2019
DOI: 10.21608/svu.2019.16763.1028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prebiotic on the Behavioural Patterns, Performance, Carcass Characteristics, Antibody Titer and Some Blood Parameters of Mule Ducks

Abstract: This study was conducted to investigate the effects of dietary supplementation of prebiotic on behavioural patterns performance and some blood parameters of ducks. A total of forty-eight 15 days-aged ducks (Mule) were randomly allotted to three dietary treatments containing 0 (Control), 1.5 g/ kg and 3.0 g/kg prebiotic, respectively. The results indicated that using prebiotic as a feed additive at a dose of 1.5 g/kg effect on duck movement activities as it increased walking and standing activities, while it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…may be attributed to stimulated growth of the beneficial microflora in the gastrointestinal tract (GIT) induced by dietary supplementation of MOS or MOS+ Enzyme (Cinar et al, 2009), or could be attributed to the growth promoting ability via the prevention and treatment of subclinical infections (Ao et al, 2011a, 2011band Toghyani et al, 2011. The current results in disagreement with Salehimanesh et al (2016) who suggested that, the dietary supplementation of MOS and B-glucan did not affect body weight and gain of broiler and (Mahmoud et al, 2020) who indicated that the addition of MOS with B-glucan had no significant effect on duck body weight and gain. Also, Kamel and Mohamed (2016) and Garipoglu et al (2006) showed that the lowest value of final body weight and weight gain at six weeks of age found for checks fed basal diet with enzyme supplementation compared to control or other feed additives.…”
Section: Productive Performance : Growth Measurementscontrasting
confidence: 96%
“…may be attributed to stimulated growth of the beneficial microflora in the gastrointestinal tract (GIT) induced by dietary supplementation of MOS or MOS+ Enzyme (Cinar et al, 2009), or could be attributed to the growth promoting ability via the prevention and treatment of subclinical infections (Ao et al, 2011a, 2011band Toghyani et al, 2011. The current results in disagreement with Salehimanesh et al (2016) who suggested that, the dietary supplementation of MOS and B-glucan did not affect body weight and gain of broiler and (Mahmoud et al, 2020) who indicated that the addition of MOS with B-glucan had no significant effect on duck body weight and gain. Also, Kamel and Mohamed (2016) and Garipoglu et al (2006) showed that the lowest value of final body weight and weight gain at six weeks of age found for checks fed basal diet with enzyme supplementation compared to control or other feed additives.…”
Section: Productive Performance : Growth Measurementscontrasting
confidence: 96%